Recovering the Piedmont past : unexplored moments in nineteenth-century Upcountry South Carolina history - Grady, Timothy Paul; Walker, Melissa, 1962- (The University of South Carolina Press, 2013)
The history of South Carolina's lowcountry has been well documented by historians, but the upcountry - the region of the state north and west of Columbia and the geologic fall line - has only recently begun to receive extensive scholarly attention. The essays in this collection provide a window into the social and cultural life of the upstate during the nineteenth century. The contributors explore topics ranging from the history of education in the region to the pugnacity of the Scots-Irish, from post-Civil War occupation by Union troops to upcountry tourism, from the Freedman's Bureau's efforts to educate African Americans to the complex dynamics of lynch mobs in the late nineteenth century. This book illustrates larger trends of social transformation occurring in the region at a time that shaped religion, education, race relations, and the economy well into the twentieth century. The essays add depth and complexity to our understanding of nineteenth century southern history and challenge accepted narratives about a homogeneous South. Ultimately, each of the eight essays explores little known facets of the history of upcountry South Carolina in the nineteenth century. The collection includes a foreword by Orville Vernon Burton, professor of history and director of the Cyberinstitute at Clemson University. -- Provided by publisher.